Distinct genetic architectures for syndromic and nonsyndromic congenital heart defects identified by exome sequencing - Sifrim, Alejandro; Hitz, Marc-Phillip; Wilsdon, Anna; Breckpot, Jeroen; Turki, Saeed H Al; Thienpont, Bernard; McRae, Jeremy; Fitzgerald, Tomas W; Singh, Tarjinder; Swaminathan, Ganesh Jawahar; Prigmore, Elena; Rajan, Diana; et al. (Nature Publishing Group, 2016)
Congenital heart defects (CHDs) have a neonatal incidence of 0.8–1%. Despite abundant examples of monogenic CHD in humans and mice, CHD has a low absolute sibling recurrence risk (~2.7%), suggesting a considerable role for de novo mutations (DNMs) and/or incomplete penetrance. De novo protein-truncating variants (PTVs) have been shown to be enriched among the 10% of 'syndromic' patients with extra-cardiac manifestations. We exome sequenced 1,891 probands, including both syndromic CHD (S-CHD, n = 610) and nonsyndromic CHD (NS-CHD, n = 1,281). In S-CHD, we confirmed a significant enrichment of de novo PTVs but not inherited PTVs in known CHD-associated genes, consistent with recent findings. Conversely, in NS-CHD we observed significant enrichment of PTVs inherited from unaffected parents in CHD-associated genes. We identified three genome-wide significant S-CHD disorders caused by DNMs in CHD4, CDK13 and PRKD1. Our study finds evidence for distinct genetic architectures underlying the low sibling recurrence risk in S-CHD and NS-CHD.